Jealousy as a correlate of intimate partner homicide‐suicide versus homicide‐only cases: National Violent Death Reporting System, 2016–2020 - Johnson, Laura (Suicide & life-threatening behavior, 2024)
Introduction The objective of this study was to compare jealousy as a correlate of intimate partner homicide‐suicide cases to homicide‐only cases using data from the National Violent Death Reporting System (NVDRS), a state‐based surveillance system maintained by the Centers for Disease Control and Prevention. Jealousy is categorized as jealous feelings or distress over a current or former intimate partner's relationship or suspected relationship with another person. Methods NVDRS data from a 5‐year period (2016–2020) was used to estimate frequencies and identify significant differences in jealousy and other sociodemographic, mental health, relationship, and incident‐related correlates of intimate partner homicide‐suicide compared to homicide‐only cases. Cases were included if they involved an intimate partner single homicide or a single homicide followed by suicide. Results The study sample included 5335 cases (intimate partner homicide‐suicide n = 1402; homicide‐only n = 3933). A significantly higher percentage of intimate partner homicide‐suicide cases reported jealousy preceding the event (9%) compared to homicide‐only cases (6%). Compared with homicide‐only cases, homicide‐suicide cases had 3.5 greater odds of recording jealousy as a precipitating event. Conclusion Findings suggest that intimate partner homicide‐suicide cases are distinct from homicide‐only cases both in terms of individual‐ and incident‐level and situational factors, including the presence of jealousy.